Elevated homocysteine levels in patients with heart failure: A systematic review and meta-analysis. Issue 33 (20th August 2021) - Jin, Nake; Huang, Lei; Hong, Jun; Zhao, Xuechen; Chen, Yujiao; Hu, Jianan; Cong, Xin; Xie, Yuquan; Pu, Jun
Abstract: Background: Elevated homocysteine (Hcy) levels showed increasing significance as the predisposing factor for the pathogenesis of atherosclerotic sequelae, including cardiovascular mortality, coronary artery disease, and stroke. There is increasing evidence linking plasma Hcy levels and heart failure (HF). The association between the elevated level of plasma Hcy and HF was examined by meta-analysis and systematic review in this study. Methods: The PubMed and ScienceDirect databases until April 2020 were utilized to collect previous literature on plasma Hcy levels and the potential relation to HF. The pooled effects were evaluated depending on standardized mean differences (SMDs) with 95% confidence intervals (CIs), and the calculation was performed using Stata 12 software. Potential sources of heterogeneity were assessed with subgroup analysis and sensitivity analysis. Results: A total of 12 research projects including 5506 subjects were selected. For pooled effect, the results confirmed that patients with HF had higher Hcy levels than the control subjects (SMD, 1.148 and 95%CI, [0.715, 1.581]). Based on the classification of New York Heart Association (NYHA), the Hcy levels for the group of NYHA I or II (SMD, 1.484 and 95% CI, [0.442, 2.527]) and the group of NYHA III or IV (SMD, 3.361 and 95% CI, [1.902, 4.820]) were significantly increased compared to controls, while the increase was more intensive for the group of NYHA III or IV. Subgroup analyses revealed similar results. Conclusion: Our meta-analysis identified that plasma Hcy levels were significantly elevated in HF patients compared to control subjects, which is positively related to the advancement of NYHA class.